Research on Comprehensive Survey Methods for Mined-out Areas - Liu, Dongcheng (Journal of Research in Science and Engineering, 2026)
With the continuous expansion of China's railway coverage across the country, railway construction inevitably passes through various underground mineral development areas. Thus, the issue of goaf areas resembles "geological reefs," posing a threat to the safety of railway operations. To more accurately and efficiently detect the location and influence scope of goaf areas, this paper systematically introduces comprehensive investigation methods and techniques, including data collection, field surveys, geophysical exploration, D-InSAR, and drilling. Through systematic comprehensive investigation, not only can the location of goaf areas be accurately determined, but their influence scope can also be delineated, providing assurance for assessing the safety of railway lines traversing goaf areas.